Social groups barely change the speed-density relationship in unidirectional pedestrian flow, but affect operational behaviours. (July 2021) - Hu, Yanghui; Zhang, Jun; Song, Weiguo; Bode, Nikolai W.F.
Highlights: The effect of social groups on unidirectional pedestrian flow is tested. Pedestrian densities are varied experimentally. Macroscopic dynamics are affected by social groups, but the effect is weak. Clear differences in movement dynamics exist between individuals and groups. The need for considering groups thus depends on the safety context. Abstract: Pedestrian crowds are not homogeneous. One common distinguishing characteristic is the membership in social groups based on friendship or families, for example. It is important to understand how these social groups affect pedestrian dynamics to inform their consideration in safety planning. Despite previous work on social groups, there is a paucity of controlled experiments on their effect under normal conditions which is crucial to delineate relative risks to pedestrians in non-emergency situations. To address this, we present results from controlled experiments on the influence of dyadic social groups in unidirectional pedestrian flow. We consider crowds comprised of 100%, 67%, or 0% social groups. Our experimental setting results in crowd densities between 1.25 and 4.0 pedestrians per m 2 . We find that while the relationship between pedestrian speed and density is affected by the presence of social groups, the size of this effect is smaller than the overall variability of observations. In contrast, we find clear differences in movement dynamics between individuals and social groups. Social groups move at slower speeds and overtake others less frequently. Regardless of pedestrian density, social groups are further away from the next-closest pedestrian than individuals are, suggesting there is a larger empty space around social groups. These findings suggest when social groups need to be considered in safety management and modelling under normal conditions. At a macroscopic level, described by speed-density relationships, social groups need not be considered explicitly but when considering a microscopic level, including overtaking and personal space, they should be considered explicitly.